Penggunaan Media Pembelajaran Spinning Wheel dalam Pembelajaran Qawa>id Nahwu - Nisa Fahmi Huda (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
Arabic is a field of study that is taught at the junior high school level or equivalent. Arabic learning at this level is directed at mastering the four language skills which include listening skills, speaking skills, reading skills and writing skills. However, apart from these four skills, there are also several elements that we need to pay attention to the rules. This study aims to determine the effectiveness of the use of the spinning wheel media in learning Arabic, especially qawaid nahwu. The methods of collecting data are observation, interviews, tests, and documentation. The approach used is descriptive quantitative with percentage calculations. The result of this research is that the use of the spnning wheel media can improve the qawaid nahwu learning process in the seventh grade training of students of the Darul Qur'an Wal Islamic Boarding School.